Analisis Usability Menggunakan Metode Heuristic Evaluation Pada Aplikasi Mobile Bahasa Isyarat Tuna Rungu Wicara (Studi Kasus: Aplikasi AKRAB) - Muhammad Hidayat; Wildan Suharso; Briansyah Setio Wiyono (Universitas Muhammadiyah Malang, 2024)
Heuristic Evaluation is a technique for examining and analyzing usability problems in interface design based on Usability Heuristics. Heuristic evaluation is very suitable for interface research because it has more structure and direction compared to other methods. To find usability problems more easily, heuristic evaluation is recommended when using design evaluation techniques. Therefore, it is necessary to carry out a usability analysis on AKRAB aplication because this application has direct interaction with users so quality control must be carried out to find out whether it is effective and efficient so that it always develops according to user needs. This research applies 10 principles of usability heuristic evaluation by using experts or people who are experts in the field of user interface or user experience as respondents. Based on the evaluation results, it produces a total usability value of 1.96, while the total usability value of the accessibility heuristic is 1.63, meaning that low priority improvements are needed. In these results, 3 aspects were found with the highest level of problems, namely Error Prevention with a value of 3.2, Flexibility and efficiency of use with a value of 2.8, and User Control and freedom with a value of 2.6, which means there is a problem that is disturbing the user so improvements are needed. with low priority. Then, 6 aspects were found with a moderate level of problem with a severity rating of 2, which means repairs were carried out with low priority. Apart from that, 1 was found, namely Aesthetic and minimalist design with a severity rating value of 0.33, which means there are no problems or the system is comfortable to use.